Parallel-Serial Production Systems with Many Working Memories - Uhr, Leonard (University of Wisconsin-Madison Department of Computer Sciences, 1978)
This paper describes several extensions to standard Production System (PS) languages that appear to make them more conveniently usable for a wider variety of perceptual and cognitive systems. The extensions are described (to para1lel productions, mu1tiple memories, and productions that are implied by productions), and a programming language ((PS)2MnP) is presented that incorporates them. Sketches are given indicating how several different kinds of cognitive and perceptual systems might be coded in this extended language, and suggestions are made as to additional extensions that might further augment the power and convenience of such a language.